Inkonsistensi Kebijakan Penggunaan Jaring Trawl (Studi Kasus Penggunaan Jaring Trawl oleh Nelayan Wilayah Perairan Gresik) - Arisandi Arisandi (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2016)
This study aimed to determine the shape of inconsistency of utilization trawl nets policy in Gresik Regency. This research used descriptive qualitative. Sources of data is collected primary data through interview that is submitted to the Kasat Polair Polres Gresik, Kaur Binops Satpolair Polres Gresik, Kanit Gakkum Satpolair Polres Gresik and those involved in illegal fishing. The research showed that (1) fishing in using trawl nets as habit in one of areas in the waters Gresik, so Regulation of Marine and Fisheries Ministry Number 2 on 2015 of Prohibition of Utilization Hela Trawl Fishing Equipment and Trawl Drag (Seine Nets) in Republic Indonesia Water in accordance with mandate on the article 9 of Law Number 45 of 2009 to be less impact on the reduction of fishing in using trawl nets. (2) The government's attitude did not tight; it is caused incosistency towards prohibition on the use of trawl nets in fishing effort in the territorial waters Gresik. Although it has been banned, but in the end the government in this regard as relented and eventually tolerate even within certain time limits. (3) The fact, incosistency made it difficult taking firm steps to follow up on illegal fishing violations that occurred in the waters of Gresik